2019
DOI: 10.1007/s40544-019-0270-x
|View full text |Cite
|
Sign up to set email alerts
|

Friction of metal-matrix self-lubricating composites: Relationships among lubricant content, lubricating film coverage, and friction coefficient

Abstract: Metal-matrix self-lubricating composites can exhibit excellent tribological properties owing to the release of solid lubricant from the matrix and the formation of a lubricating film on the tribosurface. The coverage of the lubricating film on a worn surface significantly influences the sliding process. However, it is difficult to quantify the film coverage owing to the thin and discontinuous character of the lubricating film and the high roughness of the worn surface. A quantitative characterization of the lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 36 publications
(31 reference statements)
0
13
0
Order By: Relevance
“…The lubricating film containing rich solid lubricants can shear easily, which reduces the friction coefficient of the nanocomposite [3,23]. The transfer film on the worn counter disc surface has also been reported in other studies on metal matrix self-lubricating composites [7,13,23].…”
Section: Wear and Friction Propertiesmentioning
confidence: 55%
See 3 more Smart Citations
“…The lubricating film containing rich solid lubricants can shear easily, which reduces the friction coefficient of the nanocomposite [3,23]. The transfer film on the worn counter disc surface has also been reported in other studies on metal matrix self-lubricating composites [7,13,23].…”
Section: Wear and Friction Propertiesmentioning
confidence: 55%
“…When the concentration of solid lubricants in metal matrix self-lubricating composites is greater than 5 wt%, the lubricating effect of the solid lubricants is more pronounced, as reported by Wu et al [17]. Xiao et al [7] synthesized Cu-MoS 2 composites by hot-press sintering, and their results indicated that the friction coefficient and wear rate of Cu-MoS 2 composites reduced by 81.6% and 96.0% when the MoS2 content was increased from 0 vol% to 40 vol%, respectively. More recently, lubricating films on worn surfaces have garnered significant attention [18][19][20].…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…Besides, lubricants which mainly include solid lubricants and liquid lubricants are widely used for lubrication. There are many advanced solid lubricants such as molybdenum disulfide (MoS 2 ) film [7], diamond-like coating [8], entangled carbon nanotube (CNT) film [9], and polymer material [10,11]. However, their tribological properties are directly influenced by the friction environment, and they are prone to being a wear-out failure after serving for a long time.…”
Section: Frictionmentioning
confidence: 99%